¬pV¬qV¬r is equivalent to ¬pV(¬qV¬r) is equivalent by commutation to ¬pV(¬rV¬q) is equivalent by material implication to ¬pV(r ->¬q)
________________________________ From: Alex Tank <email@example.com> To: firstname.lastname@example.org Sent: Monday, 24 September 2012, 18:57 Subject: Need help w/ problem
Hi all, back at math after a couple years break (even though I dont think the math I took would help with this). Anyway I'm just starting out with propositional equivalences and i needed help with this more intermediate problem. Any help would be greatly appreciated :) Show that the compound propositions ¬p V ¬q V ¬r and ¬p V (r -> ¬q) are equivalent.